Perancangan Alat Inovasi pembacaan hasil ukur debit dan volume air kencing menggunakan wireless dan printer pada uroflowmetry - Dinyo Mikananta Rifaco; Mohammad Rofi’i; Florentinus Budi Setiawan (Asosiasi Dosen Muda Indonesia, 2025)
Urinary Tract Infections (UTIs) can be identified through several indicators, such as difficulty urinating, weak urine flow, and low urine volume. To enhance the diagnosis and monitoring of this condition, a wireless-based uroflowmeter equipped with a thermal printer has been developed. This device utilizes a YF-S401 flow sensor to measure urine flow rate and volume, with pulse outputs processed by an Arduino UNO microcontroller. A Bluetooth module (HC-05) is used for wireless data transmission to an Android-based application (developed using App Inventor), while the measurement results can also be printed via a thermal printer. Volume testing demonstrated low error rates (0.33% – 1.53%), and flow rate testing produced results close to actual values. The device successfully connected wirelessly to the application and printed data accurately, indicating that it is suitable for supporting uroflowmetry examinations.